Flow cytometry method for determining the kariotype of tea somatic clones isolated in vitro (camellia sinensis (l.) O. Kuntze) - M. V. Gvasaliya; L. S. Samarina (Новые технологии, 2019)
The method of flow cytometry (on Beckman Coulter company cytometer) has been used to study the genetic variation of the karyotype in 15 somatic clones of tea plants isolated in vitro. Somatic clones have been obtained by inducing gemmogenesis from a callus culture of tea micro sprouts, which have been in vitro root-to-seed for 8 years. The Murashige and Skoog modified mineral base (MS) with an addition of growth regulators of 6 – BAP – 2,5 ml + NAA – 0,2 ml + HA – 1,0 ml + mesoinositol – 100 mg have been the basic nutrient medium for cultivating somatic clones. Changes in the karyotype have been recorded by analysis of the genome size. The Colchis tea genotype of 2n = 30 and the Allium cepa 2n = 18 monitor sample (32,07 pg DNA) have been used as external standards. As a result of the studies, genome size variability has been detected in 3 of the 15 tea somatic clones. In somatic clones (Sc – 11; Sc – 27; Sc – 33) the genome size is 7,26-8,70 pg (picograms) of DNA compared with the control genotype of the diploid Colchis variety, whose genome size is 5.08 pg of DNA. The presence of somaclonal variability in somatic clones isolated by phenotypic traits (Sc – 11; Sc – 27; Sc – 33) has been confirmed at the karyotype level.